Prevalensi Analisa Aktivitas Jarak Dekat Ibu-Ibu Fatyat Nu Terhadap Kejadian Kelainan Refraksi Di Kecamatan Rungkut Surabaya - Hendra Yuda; Rachman Irwanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Close-range activities, such as reading and using electronic devices, have become basic needs, especially in urban areas. Dependence on digital devices, such as smartphones, facilitates access to information, shopping, and entertainment, but also has negative impacts, one of which is an increase in refractive disorders, especially among millennials and mothers. This condition needs to be considered and educated to prevent it from spreading. In addition to the health impacts, this dependence has triggered a potential new economy, such as online delivery services and sales, where traders can operate from home. Goods and services can be ordered and delivered easily, offering practical and economical solutions for consumers.